2019
DOI: 10.1021/acs.inorgchem.9b01059
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc Coordination Complex Mimicking Carbonic Anhydrase for CO2 Hydrolysis and Sequestration

Abstract: Carbonic anhydrase (CA) mimicking is an effective and environmentally friendly strategy for carbon dioxide sequestration. Herein, we developed a nonanuclear CA-mimetic zinc coordination complex (1) which possesses a coordination environment similar to that of CA’s catalytically active zinc sites. Complex 1 exhibited excellent reusability, solvent and thermal stability, and gram-scale synthesis, which are essential for practical applications. It was found that complex 1 exhibited outstanding catalytic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Biomimetic nanozymes are catalysts that mimic natural enzyme catalytic structures and functions, mainly including polypeptide metal complexes, small molecule metal complexes, , and nanomaterials. Compared with natural enzymes, nanozymes not only have similar catalytic activity but also have the advantages of easy synthesis and high stability . Till now, several biomimetic CA analogues have been synthesized. , The zinc complex of 1,4,7,10-tetraazacyclododecane is considered one of the most representative functional models of biomimetic CA . Floyd et al found that the 1,4,7,10-tetraazacyclododecane chelate of zinc­(II) perchlorate (zinc rings) was highly stable and could be used as a powerful catalyst for industrial carbon capture .…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic nanozymes are catalysts that mimic natural enzyme catalytic structures and functions, mainly including polypeptide metal complexes, small molecule metal complexes, , and nanomaterials. Compared with natural enzymes, nanozymes not only have similar catalytic activity but also have the advantages of easy synthesis and high stability . Till now, several biomimetic CA analogues have been synthesized. , The zinc complex of 1,4,7,10-tetraazacyclododecane is considered one of the most representative functional models of biomimetic CA . Floyd et al found that the 1,4,7,10-tetraazacyclododecane chelate of zinc­(II) perchlorate (zinc rings) was highly stable and could be used as a powerful catalyst for industrial carbon capture .…”
Section: Introductionmentioning
confidence: 99%
“…The most efficient catalyst for the hydration of CO 2 is the enzyme carbonic anhydrase (CA). CA is a metalloenzyme with a Zn 2+ ion active site, while some species of the enzyme also have Fe 2+ and Cd 2+ ion active site. CA is found in most mammals and microbes for conversion of CO 2 to carbonic acid for pH regulation and CO 2 transportation . In nature CA is found as five different species that include α, β, γ, δ, and ζ .…”
Section: Catalyzed Hydration Of Co2mentioning
confidence: 99%
“…18 Considering the prominent activities afforded by these biologic catalysts, numerous efforts have been devoted in the last years to design artificial systems able to mimic enzymatic activity, the so-called synzymes. 19,20 On this behalf, two different synzymatic approaches are currently established: (I) the development of abiotic systems that contain analogous groups to the ones found in the active-site of the enzyme, [21][22][23] and (II) the design of molecules that do not necessarily resemble the active pocket but are still capable to promote the desired function through properly arranged functionalities. [24][25][26][27] We have recently reported a simple macrocyclic system that promoted superior activity in the cycloaddition of CO 2 to terminal epoxides in the presence of halide anions (Fig.…”
Section: Introductionmentioning
confidence: 99%